Fostering International Relations: The Role of Index Citra Indonesia in Advancing Indonesian Diplomacy Abroad - Paksi, Arie Kusuma; Renta, Pebria Prakarsa; Alvionita, Anisa Rahma (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
This research analyzes the role of the Index Citra Indonesia in enhancing the public diplomacy of Indonesian representative offices abroad. The focus of this study is to assess how the digital survey application, developed by the government since 2017, has been utilized to expand Indonesia's image and diplomatic reach globally. The function of the Index Citra Indonesia is to evaluate the performance of representatives through systematic data collection from respondents, covering aspects such as opinions, perceptions, and attitudes towards Indonesia. The research findings indicate the effectiveness of the Index survey in providing information related to respondent insights, which can be acted upon with the creation of long-term diplomatic strategies and programs. These programs are essential in strengthening Indonesia's public diplomacy framework to meet the needs of the international public. This study contributes to the discourse on digital diplomacy by highlighting the role of digital technology development and its impact on contemporary diplomatic practices. Keywords: Index Citra Indonesia, Public Diplomacy, Indonesian Representatives Abroad International Perceptions, Performance Improvement Penelitian ini menganalisa peran dari Indeks Citra Indonesia dalam meningkatkan diplomasi publik kantor perwakilan Indonesia di luar negeri. Fokus dari studi ini adalah untuk menilai bagaimana aplikasi survei digital, yang dibuat oleh Pemerintah sejak tahun 2017, telah dimanfaatkan untuk memperluas citra dan jangkauan diplomasi Indonesia secara global. Fungsi Indeks Citra Indonesia adalah mengevaluasi kinerja perwakilan melalui pengumpulan data sistematis dari responden, yang mencakup aspek seperti opini, persepsi, dan sikap terhadap Indonesia. Temuan penelitian menunjukkan keefektifan survei Indeks dalam memberikan informasi terkait wawasan responden, yang dapat ditindaklanjuti dengan pembuatan strategi dan program diplomasi jangka panjang. Program-program tersebut sangat penting dalam memperkuat kerangka diplomasi publik Indonesia agar sesuai dengan kebutuhan publik internasional. Penelitian ini berkontribusi pada diskursus diplomasi digital dengan menyoroti tentang peran perkembangan teknologi digital dan dampaknya bagi praktik diplomasi kontemporer. Kata-kata Kunci: Index Citra Indonesia, Diplomasi Publik, Perwakilan Indonesia di Luar Negeri, Persepsi Internasional, Peningkatan Kinerja